Hungary : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper on Hungary reports that the public enterprises may pose significant fiscal risks on account of their quasi-fiscal activities and contingent liabilities. More than 85 percent of the economy is in private hands. According to the Privatization Act, assets may remain in long-term state ownership if they belong to a national public utility provider or are considered to be of strategic importance for the national economy or defense. Capital-intensive and labor-intensive enterprises remain as state property.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet